Topical application of purple cabbage (Brassica oleracea L. var. capitata f. rubra) ethanol cream extract of dermic collagen on male Wistar rats (Rattus norvegicus) exposed to ultraviolet B - Komang Jegek Triangga Apsari; I Gusti Ayu Dewi Ratnayanti; I Gusti Komang Nyoman Arijana; I Wayan Sugiritama (Intisari Sains Medis, 2020)
Background: Purple cabbage or also known as red cabbage (Brassica oleracea L. var. capitata f. rubra) contains polyphenols, especially anthocyanin (cyanidin-3-diglucoside-5-glucoside). Anthocyanin has a protective effect against radical oxidative superoxide (ROS). Thus it can prevent skin damage caused by ultraviolet (UV)-B radiation.Aim: The research aims to prove the effectivity of distribution of purple cabbage ethanol cream extract prevented the decrease of dermal collagens on Wistar rats (Rattus norvegicus) exposed to UV-B rays.Method: This research was arranged with the randomize post-test only control group design. 30 rats were divided into 6 groups containing 5 rats each, there are control group (P1) without distribution of any cream, Treatment Group (P2) with a distribution of base cream (placebo), (P3) sunblock 33 SPF, (P4) 5%, (P5) 10 %, and (P6) 20 % smeared by purple cabbage ethanol cream extract. All groups exposed to UV-B with a total dose of 840 mJ/cm2 for 4 weeks. Then a sampling rats skin was done for examining the level of collagen skin with Sirius red staining. The level of collagen was calculated by the percentage of the area of the pixel of collagen and was compared with the pixels of entire dermal tissues.Result: The result demonstrated that the mean of collagens in The First Group/P1 (57.74%) and P2 (60.84%) decreased more significantly than P3 (82.17%), P4 (68.23%), P5 (76.93%), and P6 (84.54%) following UV-B exposure. The Post Hoc result showed that there was no significant difference in the level of collagen in the control group and placebo group and the sunblock group with the purple cabbage’s ethanol cream extract group of 20% (p>0.05).Conclusion: the distribution of purple cabbage ethanol cream extract prevented the decrease of dermal collagens on male Wistar rats skin exposed to UV-B.